Judicial Systems in Transition Economies : Assessing the Past, Looking to the Future - Anderson, James H. (Washington, DC: World Bank, 2012)
The report examines how courts have performed, and reveals their impact on public opinion and the business environment. It provides insight into linkages among reforms as well as linkages between reforms and public demand for a fair judiciary. The authors show that while each country presents different challenges and opportunities, certain lessons apply in most settings. Their insights and data would be useful to policy makers, judicial personnel, and those involved in reforming judiciaries.